A trepanated human skull from a crematory burial ground of Lusatian Culture - Karaś, Bogumiła (Anthropological Review, 1980)
In an urn excavated at a prehistoric burial ground in Opatowiec were found large fragments of a skull belonging to a female who had died at age of about 30 years. Reconstruction of the skull allowed to observe a number of craniometric characters (given in the text) and discover a circular hole made with use of some scarping bronze tool in the left parietal bone. On insides of both parietal bones were found pathological changes likely to be the cause for the trepanation.